Pengembangan Media Pembelajaran Interaktif Berbasis Adobe Flash CS3 Professional - Bella Infita Elmawati; Ali Priyono; Saihul Atho Alaul Huda (JoEMS (Journal of Education and Management Studies), 2020)
The development of interactive learning media based on Adobe Flash CS3 Professional is an effort to compile learning media with the help of operational tools in the form of Adobe Flash application. However, not all teachers have the ability to develop interactive learning media. The problem that arises is how to develop learning media for Islamic education based on adobe flash cs3 professional with Luqman Al-Hakim's example of exemplary material, the effectiveness of adobe flash cs3 based Islamic religious education learning media products. Based on these problems, the purpose of this discussion is to develop and find out the effectiveness of adobe flash cs3 professional Islamic education learning media products. This research method uses research and development methods with the research model of Borg and Gall. Sources of data in this study were subjects where data was obtained. Data collection techniques used were observation, questionnaires, interviews and documentation. Based on the results of the discussion and research, it was concluded that the development of learning media for Islamic education based on adobe flash cs3 professionals can improve the understanding of learning material in the example of Luqman Al-Hakim's example.